Generation and heterozygous repair of human iPSC lines from two individuals with the neurodevelopmental disorder, TRAPPC4 deficiency - Riley Hall; Tim Sikora; Annabelle Suter; Jia Yi Kuah; John Christodoulou; Nicole J Van Bergen (Stem Cell Research)
A rare neurodevelopmental disorder has been linked to a well-conserved splice site variant in the TRAPPC4 gene (c.454 + 3A > G), which causes mis-splicing of TRAPPC4 transcripts and reduced levels of TRAPPC4 protein. Patients present with severe progressive neurological symptoms including seizures, microcephaly, intellectual disability and facial dysmorphism. We have generated stem cells from fibroblasts of two individuals with the same homozygous TRAPPC4 c.454 + 3A > G pathogenic variant and used CRISPR/Cas9 editing to generate heterozygous gene-corrected isogenic controls. Clones were tested for pluripotency, differentiation potential, genotyped and karyotyped. These iPSC-based models will be used to understand disease mechanisms of TRAPPC4 disorder.